Clinical evaluation of a new multi-purpose disinfecting solution in symptomatic wearers of silicone hydrogel contact lenses - Garofalo, Renee; Maissa, Cecile; Corbin; Kading, David; Powell; Rosenblatt; Secor (Clinical optometry (Auckland), 2012)
Background: The purpose of this study was to evaluate the safety and efficacy of a new multi-purpose disinfecting solution containing a diblock copolymer, poly(oxyethylene)-poly(oxybutylene), designed to improve the wetting properties of silicone hydrogel lenses in patients with symptoms of discomfort. Methods: This 30-day, randomized, concurrently controlled, double-masked, multi-site study involved 589 subjects at 42 investigational sites in the US. Existing symptomatic lens wearers were randomly assigned to either regimen 1 (OPTI-FREE® PureMoist®, Alcon Laboratories Inc,) a newly developed formulation containing the diblock copolymer), or regimen 2 (renu® fresh™ multi-purpose solution Bausch + Lomb, Inc). On days 0, 14 and 30, subjects assessed acceptability and comfort using seven Likert-type questions, rated the intensity of ocular symptoms (comfort, dryness, irritation, scratchiness, burning, stinging) on a visual analog scale (0–100), as well as reported lens wearing time, comfortable lens wearing time, and rewetting drop frequency. The investigators assessed slit-lamp findings (including circumlimbal conjunctival lissamine green staining and corneal fluorescein staining), on-eye lens surface wettability and deposits, visual acuity, and adverse events. Results: Differences favoring regimen 1 were noted on Day 30 for the primary Likert statement “I can comfortably wear my lenses” (P= 0.047) and for comfortable lens wear time (P = 0.041). Symptoms of ocular scratchiness, ocular burning, and ocular stinging were all rated lower after 30 days of use by subjects using regimen 1 compared with those using regimen 2 (P ≤ 0.024). Circumlimbal conjunctival staining (sum score) was significantly lower with regimen 1 (P < 0.0001). Other parameters did not show any difference between the two treatment regimens. Conclusion: This study shows that the new multi-purpose disinfecting solution is safe and effective when used by symptomatic silicone hydrogel contact lens wearers. By improving symptoms of scratchiness, burning, stinging, and comfortable wear time, and decreasing circumlimbal conjunctival staining, the new multi-purpose disinfecting solution enhances the patient's wearing experience and helps maintain optimal lens performance.